Plány odkanalizování venkova a sucho - Plotěný, Karel; Plotěný, Michal (Akademické nakladatelství CERM, 2020)
Podle závazku při vstupu do EU má být zajištěno odpovídající řešení odpadních vod i u menších aglomerací. Což mimo jiné přispěje k dosažení dobrého stavu vod. Dalším cílem je sociálně únosná cena vody. Všechny tyto tři závazky pak v podstatě znamenají rovnici o třech neznámých, jejímž výsledkem by měl být plán jak jich dosáhnout. V České republice by měl představu konkretizovat tzv. Plán rozvoje vodovodů a kanalizací kraje (PRVK), který by měl vycházet z Plánů povodí a sociálních podmínek v příslušné oblasti. Jako rozumný postup se jeví zpracování různých variant řešení odpadních vod a jejich vyhodnocení. Závěrem by měl být akt, kterým se občané obce rozhodnou pro akceptovatelné řešení. Bohužel se tak neděje a výsledkem jsou plány, které nerespektují východiska, nebo postaví občany před hotovou věc. Příspěvek se zabývá jevy ovlivňujícími rozhodování, které ve výsledku vedou k řešením nesplňujícím okrajové podmínky. Příspěvek byl prezentován na konferenci ExFoS 2020.

According to the commitments accepted in the EU accession negotiations, the Czech Republic should provide for adequate solutions for wastewater even in smaller settlements. Apart from this, we have set the task of achieving a good condition of waters, which means to solve the rural areas on the whole. Another restriction we adopted in this process is a socially bearable price of water. In principle, all the three commitments represent an equation with three unknowns, the output of which should be a plan how to meet them. In the Czech Republic, this plan should be given by the so-called Development Plan of Regional Water &Sewer Systems (RWSS). As a prudent approach, it appears to process various options of wastewater treatment and their evaluations. In the end, there should be an act, in the course of which municipal citizens decide about a solution acceptable to them. This is unfortunately not the case and the resulting plans do not respect the ordered conditions in many cases or the citizens are informed about this as an irreversible decision often socially disadvantageous. This contribution deals with some phenomena influencing incorrect decisions. The paper was presented at the ExFoS 2020 conference.
Sewerage Plans in Rural Areas and Drought
Keywords: plány rozvoje vodovodů a kanalizací; PRVK; obec; Development plan of regional water&sewer systems; RWSS; municipality